The Effect of Wordwall Media Implementation on Fourth Grade Students' Interest in Learning Pancasila Education at SDN 25 Pulau Punjung - Yulia Darniyanti; Suci Rahma Putri; Yuli Nopita Sari (The Future of Education Journal, 2025)
This study is motivated by issues in the teaching of Pancasila Education, specifically the low student interest in learning among fourth-grade students in this subject. This is evident from the low active participation of students during the learning process. This condition requires innovation in the teaching of Pancasila Education to increase student interest in learning. This research uses a quantitative approach with an experimental research design. The population of this study consists of all fourth-grade students at SDN 25 Pulau Punjung. The sample includes 17 fourth-grade students from SDN 25 Pulau Punjung. The data collection techniques used are a learning interest questionnaire and a Wordwall implementation sheet. The data collection was conducted in the form of a 30-statement learning interest questionnaire for the fourth-grade class. The results from the independent samples t-test show a significance level of 0.000 < 0.05, indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the application of the Wordwall media has an effect on students' learning interest in Pancasila Education.